Competing security and humanitarian imperatives in the Berm - Charles Simpson (Forced Migration Review, 2018)
Approximately 60,000 Syrians are trapped in ‘the Berm’, a desolate area on the Syria-Jordan border. When security concerns are prioritised over humanitarian needs, and aid agencies turn to militant groups to deliver aid, the consequences can be deplorable.